Double-deck passenger cars of maximum possible dimension standard for the rolling stock of type Тб - Yu. M. Lazarenko; D. N. Arshintsev; I. S. Ermishkin; E. V. Kapuskina; E. A. Mitina (Вестник Научно-исследовательского института железнодорожного транспорта, 2017)
Double-deck cars of the models 61-44465, 61-4442, 61-4473, 61-4442 were designed and manufactured at the Tver Car Building Plant. Tests of dimensions of double-deck cars of Tпр dimension standard carried out on the Test Loop of JSC “VNIIZhT” confirmed their full compliance with the requirements of GOST 9238-2013 and currently they are operated on the railways of the Russian Federation. The article deals with the application of increased dimensions of the rolling stock developed by JSC “VNIIZhT” to create an innovative rolling stock. The main attention is paid to the creation of a double-deck passenger car at Tver Car Plant using the Tб dimension standard - the world's largest overall size of rolling stock. The structure clearance gauge of infrastructure facilities on the railway network provides insufficiently safe passage of cars of Tб dimensions. The article highlights activities carried out by the Central Directorate of Infrastructure of JSC “Russian Railways” to check the actual dimensions of structures and devices on the routes of trains with double-deck cars of Tб dimension, as well as to expand the range of double-deck cars of Tпр standard being already in operation. Identified in the operation of double-deck cars of model 614465 (72, 73, 92) passenger discomfort on the upper berth of the second deck compartment of car with Tпр dimension standard the Tver Car Plant decided to eliminate due to application of dimensions Tб. It should be separately noted that the use of this dimension creates conditions for solving the problem of providing temperature control in the car. The requirements developed by JSC “VNIIZhT” for the actual structure clearance gauge for the passage of cars of Tб dimensions have been accepted by JSC “Russian Railways” for the preparation of circulation of double-deck trains of Tб dimension standard.